“Sikatan” (Sikat Gigi Anak Teratur dan Menyenangkan) : Upaya Peningkatan Perilaku Hidup Bersih dan Sehat melalui Edukasi Kesehatan gigi di Desa Jatisari - Aqilla Fibri Khairani; Anjarika Dwi Rahmawati; Febisanda Adila Nuha; Ainniyah Wulandari Kusuma; Yunita Khoirunnisa; Nur Safitri; Shanti Akhiriani (Dental Agromedis, 2025)
Dental and oral health is an important part of general health that affects the quality of life of the community. Many residents of Jatisari Village, Tempeh Subdistrict, Lumajang Regency still experience dental and oral problems. Seeing this problem, KKN-K 029 students initiated the “SIKATAN” (Regular and Fun Children's Toothbrushing) Program as an effort to improve clean and healthy living behaviors from an early age. The objective of this activity is to increase the knowledge, skills, and awareness of elementary school/MI students in Jatisari Village regarding the importance of maintaining dental and oral health through interactive, enjoyable, and age-appropriate educational methods. The implementation method includes a pre-implementation stage involving coordination with village and school officials, preparation of educational media, and internal team task distribution. The implementation phase was carried out in three schools over six days, with a series of activities including counseling, toothbrushing practice using false teeth, quizzes, educational games, fun exercises, and puppet shows. Formative evaluation was conducted after the entire series of activities was completed, focusing on the achievement of program objectives. The results of the activity showed an increase in students' knowledge about the frequency, appropriate timing, and technique of toothbrushing. Through hands-on practice, most students were able to improve their toothbrushing techniques. Toothbrushing practice and puppet shows were proven to increase enthusiasm, concentration, and retention of dental health messages. The “SIKATAN” program successfully became a model for fun and effective dental health education with the potential for long-term impact in improving the health of the village community.Keywords: dental health, counseling, SIKATAN